A model of the EFA liabilities - Francisco Rivadeneyra; Oumar Dissou (Bank of Canada, 2011)
The authors describe the liabilities model of the Exchange Fund Account (EFA). The EFA is managed using an asset-liability matching framework that requires currency and duration matching of both sides of the balance sheet. The model chooses the mix of liabilities across instruments and tenors that maximizes the return of the fund subject to a fixed asset-allocation rule and duration matching. The model considers two types of instruments: cross-currency swaps and global bonds. The main trade-off in the model is the cost advantage of cross-currency swaps relative to global bond issuance. Cross-currency swaps are, on average, a cheaper source of funding, but carry counterparty risk. The model penalizes a skewed maturity profile of liabilities because it carries rollover risks. The model also reports the implied asset-liability gap, which is a function of the total amount of cross-currency swaps.
Keywords: G32; G12; 330; Foreign reserves management; Debt management